1972
DOI: 10.2307/2272747
|View full text |Cite
|
Sign up to set email alerts
|

Decidability of some intuitionistic predicate theories

Abstract: Suppose T is a first order intuitionistic theory (more precisely, a theory of Heyting's predicate calculus, e.g., abelian groups, one unary function, dense linear order, etc.) presented to us by a set of axioms (denoted also by) T.Question. Is T decidable?One knows that if the classical counterpart of T (i.e., take the same axioms but with the classical predicate calculus as the underlying logic) is not decidable, then T cannot be decidable. The problem remains for theories whose classical counterpart is decid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Our results adapt and generalize the undecidability proof of TAUT ] sketched in [7]. Consider a generic formula A in the classical theory CE of two equivalence relations ≡ 1 and ≡ 2 .…”
Section: Undecidability Resultssupporting
confidence: 74%
“…Our results adapt and generalize the undecidability proof of TAUT ] sketched in [7]. Consider a generic formula A in the classical theory CE of two equivalence relations ≡ 1 and ≡ 2 .…”
Section: Undecidability Resultssupporting
confidence: 74%
“…It has not been difficult to show that the sets of valid formulas in G ω and in G [0,1] are identical, and both are known today as "Gödel logic". 1 Later it has been shown that this logic is also characterized as the logic of linearly ordered intuitionistic Kripke frames (see [15], [16]). Gödel logic is probably the most important intermediate logic, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Our proof adapts and generalizes the undecidability proof sketched in [8] for monadic 'LC with constant domains', which coincides with monadic G [0,1] . With the notable exception of G ↑ , all infinite-valued Gödel logics satisfy the above condition on V , see Corollary 1.…”
Section: Undecidability Of Infinite-valued Gödel Logicsmentioning
confidence: 63%